Estado hídrico y demanda de fotosintesis de Quercus ilex, Quercus faginea y Pinus halepensis MICORRIZADOS ARTIFICIALMENTE CON Tuber melanosporum EN VIVERO - DOMÍNGUEZ, J A; R. PLANELLES; RODRÍGUEZ BARREAL, J A; SAÍZ DE OMEÑACA, J A; ZAZO, J; TEYSSIERE, M; MARTINEZ, G; PINAZO, O (III Congreso Forestal Español Congreso, 2001)
We have been carried out a periodic control in Quercus ilex, Quercus faginea and Pinus halepensis inoculated with Tuber melanosporum Vitt. during the first year of growth in nursery with a water-non stressed régime; in all the species, the minimum water potential and transpiration rate didn't reflect any differences for the treatment, but in some cases, the photosynthesis rate was major in inoculated seedlings. K.W.:
Keywords: ectomycorrhiza; photosynthesis; Pinus halepensis; Quercus faginea; Quercus ilex; Tuber